2019
DOI: 10.4103/jispcd.jispcd_220_18
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic clasp cast partial denture

Abstract: Denture esthetics as defined by Glossary of prosthodontics terms the effect produced by a dental prosthesis that affects the beauty and attractiveness of the person. [ 1 ] Removable partial dentures (RPDs) are the widely accepted and treatment of choice for most cases as it is both effective and affordable. Partially edentulous treatment planning includes both esthetics and masticatory function. A prosthesis that is highly esthetic will improve patient's motivation and acceptance. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Various studies have stated that patients fail to wear partial dentures as they find the display of the clasps which act as direct retainers esthetically unacceptable. 8 A similar concern was raised by the patient which led to the decision to use aesthetic alternative for clasp assemblies. Technopolymer clasps manufactured from thermoplastic acetal resin (POM) help in overcoming the esthetics concerns of removable partial denture.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various studies have stated that patients fail to wear partial dentures as they find the display of the clasps which act as direct retainers esthetically unacceptable. 8 A similar concern was raised by the patient which led to the decision to use aesthetic alternative for clasp assemblies. Technopolymer clasps manufactured from thermoplastic acetal resin (POM) help in overcoming the esthetics concerns of removable partial denture.…”
Section: Discussionmentioning
confidence: 98%
“…They can be used in larger and deeper undercuts because of low modulus of elasticity and in situations where esthetics and periodontal health are priorities. 8…”
Section: Discussionmentioning
confidence: 99%
“…Agerberg and Carlsson reported that esthetics should be prioritised than function in prosthodontic patients. 5 Numerous patients fail to wear the partial dentures as they find the display of clasp assemblies esthetically unacceptable. 6 Ali Afzal Khan et al reported an increase in esthetics and masticatory efficiency following treatment with CPD to replace missing teeth in a partially edentulous individual.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the challenge is to recreate the retentive features of crown in accordance with clasps and minor connector of an existing partial denture without compromising aesthetics. Aesthetics of the restoration has an important role in the psychological acceptance of the prosthesis by the patient 4,5 . The literature is abundant on the retrofitting of a crown under an existing CPD clasp assembly [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%